The retail bank interest rate pass-through: The case of the euro area during the financial and sovereign debt crisis - Matthieu Darracq Pariès; Diego Moccero; Elizaveta Krylova; Claudia Marchini (European Central Bank (ECB), 2014)
This paper analyses the cross-country heterogeneity in retail bank lending rates in the euro area and presents newly developed pass-through models that account for the riskiness of borrowers, the balance sheet constraints of lenders and sovereign debt tensions affecting interest rate-setting behaviour. Country evidence for the four largest euro area countries shows that downward adjustments in policy rates and market reference rates have translated into a concomitant reduction in bank lending rates. In the case of Spain and Italy, however, sovereign bond market tensions and a deteriorating macroeconomic environment have put upward pressure on composite lending rates to non-financial corporations and households. At the same time, model simulations suggest that higher lending rates have propagated to the broader economy by depressing economic activity and inflation. As a response to increasing financial fragmentation, the ECB has introduced several standard and non-standard monetary policy measures. These measures have gone a long way towards alleviating financial market tensions in the euro area. However, in order to ensure the adequate transmission of monetary policy to financing conditions, it is essential that the fragmentation of euro area credit markets is reduced further and the resilience of banks strengthened where needed. Simulation analysis confirms that receding financial fragmentation could help to boost economic activity in the euro area in the medium term.
Keywords: J64; 330; bank lending rates; DSGE models; financial fragmentation; monetary policy; pass-through models